Evaluation of Learning Approaches among First-Year Medical and Dental Students of a Private University, in Malaysia - George, Sherly Deborah; Maung Maung , Theingi; Narayanam, Harini; Latt, Swe Swe (IIUM Medical Journal Malaysia, 2023)
INTRODUCTION: Every learner has a way of interacting with the knowledge they have acquired, and this interaction is called a learning approach. Knowing the student’s favorite learning methods will facilitate them with directions tailored to their unique needs. This study aims to measure the differences in learning approaches among first-year medical and dental students of a private university, in Malaysia. MATERIALS AND METHODS: A three-month analytical cross-sectional study was undertaken among the interested students. The self-administered, validated ASSIST questionnaire was used to measure students’ preferred learning approaches. The Pearson correlation and independent sample t-test were used to analyze the data with SPSS software. The p-value was set at less than 0.05 to indsicate a significant level. RESULTS: A total of 225 students participated, out of which 150 (66.7%) respondents were medical students, and 75 (33.3%) were dental students. Medical students reported a favoured considerably deep learning approach over dental students (t=2.874, p=0.004), and preferred the strategic approach to learning (t=2.051, p=0.041). There was a weak and no significant correlation between the concept of learning (learning as reproducing knowledge [RK] p=0.377, learning involving personal understanding [PU] p=0.269), self-rating (p=0.824), and the surface learning approach. Both medical and dental students have no significant difference in surface learning approach with t =0.556 and p=0.579. CONCLUSION: Medical students favoured deep and strategic learning over dental students. While there was no significant difference in the surface learning approach, the deep and strategic learning approaches were substantially connected with the notion of learning, types of courses/teaching, and self-rating. The knowledge of learning approaches will assist educators in making efforts to address students through successful teaching strategies. Once teachers understand the need to accommodate individual strengths and needs, they will devise appropriate new teaching methods.